2013
DOI: 10.1016/j.bpj.2012.11.3831
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Proteorhodopsin Oligomers

Abstract: Oligomerization has important functional implications for many membrane proteins. However, obtaining structural insight into oligomeric assemblies is challenging, as they are large and resist crystallization. We focus on proteorhodopsin (PR), a protein with seven transmembrane α-helices that was found to assemble to hexamers in densely packed lipid membrane, or detergent-solubilized environments. Yet, the structural organization and the subunit interface of these PR oligomers were unknown. We used site-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 53 publications
2
79
0
Order By: Relevance
“…However, because the cells do not synthesize retinal, an alternative role for the actinorhodopsin apoprotein cannot be ruled out. Many microbial rhodopsins oligomerize in the membrane and form large aggregates (55)(56)(57)(58)(59)(60). Without a cofactor, actinorhodopsin might still aggregate in the membrane, providing structural stability against membrane stresses.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the cells do not synthesize retinal, an alternative role for the actinorhodopsin apoprotein cannot be ruled out. Many microbial rhodopsins oligomerize in the membrane and form large aggregates (55)(56)(57)(58)(59)(60). Without a cofactor, actinorhodopsin might still aggregate in the membrane, providing structural stability against membrane stresses.…”
Section: Discussionmentioning
confidence: 99%
“…3A); in contrast, it is suggested that KR2 forms pentamers (Fig. 3B), and PRs assemble into pentamers or hexamers [32,[38][39][40] (Fig. 3C).…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 96%
“…G-PR likely acts as a light-driven proton pump that enables bacteria to harvest solar energy in a useable form (DeLong and Bé jà , 2010), but it displays many unique properties that suggest differences in mechanism or function from the well-studied bacteriorhodopsin proton pump (Hempelmann et al, 2011;Lö rinczi et al, 2009;Schä fer et al, 2009). Prior studies have demonstrated that G-PR assembles into hexamers in both 2D crystalline lipids (Klyszejko et al, 2008) and detergent micelle environments (Hoffmann et al, 2010;Stone et al, 2013). Although the functional implications of this assembly are still being investigated, few precise details of the G-PR oligomer structure are currently available.…”
Section: Introductionmentioning
confidence: 97%
“…A recent crystal structure (Ran et al, 2013) reveals a doughnutshaped hexameric assembly for blue-absorbing proteorhodopsin (B-PR), a protein that is homologous to G-PR but differs in its maximum absorption wavelength and photocycle timescale (Hillebrecht et al, 2006;Xi et al, 2008). However, in G-PR hexamers, there has been only a single measurement of a short interprotein distance, which identified a radial orientation of the protein within the hexamer (Stone et al, 2013).…”
Section: Introductionmentioning
confidence: 98%